Prevalence of Upper Respiratory Tract Infections Before, During, and After the COVID-19 Pandemic in Germany: A Cross-Sectional Study of 2 167 453 Outpatients - Sven H. Loosen; Wolfgang Plendl; Marcel Konrad; Christian Tanislav; Tom Luedde; Christoph Roderburg; Karel Kostev (SAGE Publishing, 2023)
Background: Although the burden of the COVID-19 pandemic on global healthcare systems is declining, long-term sequelae such as long COVID syndrome and other disease dynamics not primarily associated with COVID-19 remain a challenge. Recent data suggest that the incidence of non-COVID upper respiratory tract infections (URTI) is increasing sharply in the post-pandemic period, but there is a lack of real-world data from Germany in this respect. Methods: This cross-sectional study evaluated the number of patients with a diagnosis of URTI from the Disease Analyzer database (IQVIA) between January 2019 and December 2022. The number of UTRI diagnoses per practice and the duration of sick leave per patient were compared over time. Results: A total of 1 872 935 individuals (1 403 907 patients from general practices (GP) and 469 028 patients from pediatric offices) were included, 48% of whom were female. The number of URTI patients per practice was significantly higher in 2022 than in 2019 (732 vs 464, 58%, P  < .001), and this was observed for both women (56%, P  < .001) and men (60%, P  < .001). The post-pandemic increase in the number of URTI diagnoses correlated with age and was highest in the age group between 18 and 30 years (22%, P  < .001) and lowest in older patients >70 years (3%). In pediatric patients (<18 years), the increase was highest in the age group ≤5 years (89%). Both the number of patients per practice on sick leave due to URTI (184 vs 92) and the average duration of sick leave (+2 days) increased from 2019 to 2022. Conclusion: Our data suggest a dramatic increase in the incidence of URTI among all demographic subgroups in Germany between 2019 and 2022, which was associated with a tremendous impact on socioeconomic variables such as the frequency or duration of sick leave. These data could be of great importance in current pandemic management and the management of future pandemics.